VALIDITAS INSTRUMEN PENILAIAN AUTENTIK PADA MODEL POE MATERI FLUIDA DINAMIS KELAS XI SMA - Yanuar, Dinda; Festiyed, Festiyed (EduFisika: Jurnal Pendidikan Fisika, 2024)
The era of revolution 4.0 will be marked by the development of science and technology that is increasingly rapid and advanced. The rapid development of science and technology is a challenge for the world of education. Ongoing learning must facilitate the acquisition of student skills such as collaboration, creativity, literacy, communication, and critical thinking. To answer these challenges, the government has taken various initiatives to improve the quality of education in Indonesia, including improving the curriculum, providing school facilities and infrastructure, and improving teacher professionalism. Advances in educational theory by educational professionals have also led to developing different learning models that school teachers can apply. However, one thing that has not received much attention is the assessment or assessment system. This study aimed to determine the validity of an authentic assessment of the POE model of fluid dynamics for class XI high school. The model used in this research is the ADDIE development model design. The assessment of the validity of an authentic assessment of the POE model of fluid dynamics for class XI high school, according to three experts, uses Aiken's V formula, which is 0.87 with a valid category. So that the authentic assessment of the class XI high school fluid dynamics POE model created is in the valid category.